The perceptions of teachers on the implementation of the school progression policy in primary schools - Hlasa, Boithatelo (University of the Free State, 2022)
In reaction to high repetition rates in South African primary schools, the Department of Education introduced the progression policy through the National Policy Pertaining to the Progression and Promotion (NPPPR) of learners and the National Protocol for Assessment (NPA), to serve as guidelines on how to promote and progress learners through the education system. The intention of this study was to explore the perceptions of teachers about the implementation of the progression policy. It is believed that teachers’ perceptions influence how they maximise their production, especially when confronted by unprepared learners who are not grade ready. This qualitative study provides an interpretation and analysis of teachers’ perceptions and experiences by responding to the question, What are the perceptions of teachers about the implementation of the progression policy in primary schools? Situated in an interpretive paradigm with a phenomenological design, the study explored teachers’ perceptions. The study was embedded in a social justice theoretical framework that advocates for fair treatment and participation and promotion of teachers’ human rights through being afforded recognition and freedom of speech in policies that affect them. Teachers require support, just practices and opportunities to raise their concerns in order to give effect to their role and hinder their reluctance to fulfil their job descriptions. The research was carried out with a sample of purposively selected participants, namely teachers and departmental heads. The participants’ perceptions were interrogated using semi-structured interviews and focus group discussions. Document analysis was also employed to corroborate the data gathered through interviews and focus group discussions. The NPA as well as the NPPPR were analysed. These documents guide the promotion and progression process at schools. The findings indicate that the challenges teachers are confronted with deny them the opportunity to implement the policy effectively. Teachers are not ready to accept and implement the policy, because of its effects on learners and the way teachers perceive it. Although the findings reveal that teachers had not undergone training in the implementation of the policy, some schools had remediation strategies in place to assist the affected learners. It was evident that teachers needed training, as a large number of them confessed to using the traditional one-size-fits-all approach to teaching. Teachers do not consider the range of abilities of learners, therefore learners continually fall into the progression web. The findings indicate that the progression policy degrades the quality of education if it is not implemented effectively. In South Africa, the progression policy is implemented differently in different schools. Progressed learners suffer stigma, and teachers are unable to provide the necessary support suggested by the progression policy. From the findings of the interviews, focus group discussions and document analysis, the study made several recommendations: regular monitoring of the policy by the school management team is necessary, there should be bottom-up consultation, alternative ways to teaching should be investigated, inclusive education teachers should be available at schools, and they should cater exclusively for progressed learners’ classes, and teachers’ grievances should lead to amendments to the policy.
Dissertation (M.Ed.(Education Law))--University of the Free State, 2022
Keywords: Teacher perceptions; Progression policy; Promotion in school; Retention of learners; Grade repetition; Primary schools